A robust overset assembly method for multiple overlapping bodies - Hu, Zhiyuan; Xu, Guohua; Shi, Yongjie (International journal for numerical methods in fluids, 2021)
Summary A robust overset assembly method allowing for multiple overlapping bodies is presented. This method extends the overset assembly method to deal with the interference between objects and prevents the failure of the search for donor cells due to the complex shape of the models. The donor cells are searched before identifying the boundary of the chimera interpolation. By selecting interpolation cells only in areas with donor cells, the final overset interpolation boundary cells can always find their donor cells, which prevents orphan points and achieves excellent robustness. First, the implementation of the proposed assembly method is described in detail. Subsequently, the usability and efficiency of the method are verified using several cases. Finally, the integration strategy of the computational fluid dynamics solver based on overset interpolation with the modification of the boundary type is described and verified using practical cases with overlapping bodies. The results demonstrate the applicability of the proposed overset grid assembly method. 1. We present a new overset assembly method allowing for multiple overlapping bodies by searching the donor cell before identifying the interpolation boundary. 2. It shows good ability to eliminate “isolated island” and “orphan point” problems by selecting interpolation cells only in areas with donor cells. 3. It was properly validated by several cases and the efficiency of the overset assembly was significantly higher than other similar overset assembly programs.